An Evaluation of the Treatment of Application Letters and Reports in Core Kenyan form Three English Course Books - Mwangi, Grace; Maroko, Geoffrey M.; Nthiga, Purity M. (Journal of Applied Linguistics and Language Research, 2017)
Functional writing is an important skill since it involves writing for real life purposes. It should fit the intended purpose, audience and context. Despite the centrality of this form of writing, it has been performed dismally in the Kenya Certificate of Secondary Examination every year. In a bid to understand the nature of the problem, this paper attempts an evaluation of the general presentation of skills of writing the letter of application and the report in form three and four approved English course books. Qualitative data sets were collected by administering interview schedules to teachers from three best performing public secondary schools in Nairobi County and four editors of English course books in four publishing firms. To complement qualitative data, quantitative data was collected using a checklist. Twelve form three and four English course books approved by the Kenya Institute of Curriculum Development were selected as a study sample. The form three and form four approved English course books formed the study sample. The texts were closely studied to extract linguistic tokens for analysis. The results revealed that the presentation of guidelines for writing the two functional texts displayed inconsistencies and inadequacies of relevant information. Secondly, editors have diverse opinions concerning the presentation of guidelines in the selected texts. The study recommends that revision of the course books is necessary for the improvement of the general presentation of the guidelines provided in these course books to reflect current practice in the work place.
Keywords: Functional writing skills; General presentation